CADASIL syndrome (cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy) presenting as psychosis - Mishra, Dheerendra Kumar (Gen Psychiatr, 2018)
Cerebral autosomal dominant arteriopathy with subcortical infarct and leukoencephalopathy (CADASIL) is the most common monogenic form of cerebral small-vessel disease characterised by recurrent strokes. Behavioural disturbance also presents in a significant proportion of subjects as neurotic spectrum disorders and psychotic features are rarely reported. In this case report, we highlight a 32-year-old man with CADASIL syndrome, who had overt psychotic symptoms with neurological signs later on.